THE ESTABLISHMENT OF SALES MARKUPS OF GUARANTEEING ELECTRICITY SUPPLIERS BY METHOD OF COMPARISON OF ANALOGUES: DECREASE OR INCREASE - O. O. Mozgovaya; Yu. V. Sheval (Вестник университета)
The first results of the comparative method application for fixing regulated retail markups of guaranteeing electricity suppliers in Russia have been analyzed. The goal of the comparative method adoption is the improvement of guaranteeing electricity supplier’s effectiveness. Analysis of the legislation displayed, that the comparative method normalizes the guaranteeing electricity supplier’s yardstick revenue rates and limits the retail markups increase factors, mainly by the consumer price index. However, new methodologyapplication during the transition period led to outstripping inflation growth rate of guaranteeing electricity supplier’s retail markups. It has been identified, that in most Russian regions it was caused by the base period costs diminishing and (or) ‘yardstick cost’ limits inflating. It has been assumed, that after transition period expiry default electricity supplier’s retail markups growth ratio will be comparable to the consumer price index rate.